Medicinal Agroecology Reviews, Case Studies, and Research Methodologies - Fiebrig, Immo Norman (Taylor & Francis, 2023)
agroecological systems/health, companion-planting, natural approaches + soil remediation, plant bio-active compounds, plant-based preparations, sustainable cultivation, traditional and plant derived medicines/remedies/veterinary medicine/animal homeopathy